PATTERN OF OESTRUS, OESTROUS CYCLE LENGTH AND FERTILITY RATE FOLLOWING SYNCHROMATE-B TREATMENT IN REPEAT BREEDER COWS - SELVARAJU, M; VEERAPANDIAN, C; KATHIRESAN, D; KULASEKAR, K; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
All experiment was conducted to study the effect of norgestomet ear implants on oestrus pattern and fertility rate in repeat breeder cows. A total of 32 healthy, parous, repeat breeder cows were equally divided into 2 groups as treatment and control groups. All the cows in the treatment group were treated with 6mg norgestomet ear implants on day 1 O following natural estrus. At the time of insertion of ear implant, 2ml of SMB injection was administered intramuscularly to all the cows. The implant was removed after 9 days. Al was done at 48 and 72 hours after implant removal. In control cows, without any treatment, Al was done twice at 24 hours interval. In treated cows, the mean time to onset of oestrus, duration of oestrus, mean oestrous cycle length before and after implant treatment and first service conception rate were 29.25± 0. 70 h, 26. 75± 0.68h, 19.89±0.54 and 20.00±0.30days and 43.75 per cent, respectively. The percentage of very good, good, fair and poor oestrus intensity was 81.25, 18.75, 0.00 and 0.00 in treatment group and 25.00, 75.00, 0.00 and 0.00 in control respectively. In control coos, the duration of oestrus and first service conception rate observed were 29;38±0. 77 hours and 18. 75 per cent. It is concluded that SMB treatment has improved the conception rate in repeat breeder cows when compared to control.